ANALISIS TARI PIRING KREASI SANGGAR SYOFYANI DALAM STUDI KASUS MUSIK IRINGAN TARI - Santoso, Ahmad Teguh; Wimbrayardi, Wimbrayardi (SENDRATASIK UNP, 2019)
AbstractÂ The purpose of this study is to describe results of the analysis of creative Piring Dance at Syofyani's studio in the Case Study of Dance Accompaniment which is viewed from the relationship of the dance movements to the music rhythm. This type of research was qualitative research with using a content analysis approach. The instrument of this research was the researcher and it was assisted by supporting instruments such as stationery, camera and laptop. The types of data used were primary and secondary data. Techniques of data collection were conducted by doing library research, observation, interviews and documentation. The steps to analyze data were done by collecting data, listening to audio recording, playing music, transcribing and analyzing scores. The result shows that music and Piring dance is made based on "Alam Takambang Takambang jadi Guru", therefore the process that is passed by imagining (visualizing) the movement of the dance , it is like stretching a shade (weaving place) then describing the movement above the shade. Music and Piring Dance are also made based on the nuance of music and dance that are presented and related in rhythmic between music and dance. Based on the rhythmic relationship between music and dance, there are several parts of music and dance that have strong accents so that it support the rhythm that is shown from music and dance from the intro section, core A and B and their variations. B rhythmic which is used in music uses more of a 2/4 with a different tempo from the beginning to the final climax.Â Keywords: analysis, creative Piring dance, syofyani studio, dance accompaniment music.